Influence of Polypropylene Length on Stability and Flow of Fiber-reinforced Asphalt Mixtures - Bayat, Ramin; Talatahari, Siamak (Salehan Institute of Higher Education, 2016)
Engineers are constantly trying to improve the performance of the flexible pavements. The main surface distress types which cause maintenance and disruption are rutting and fatigue cracking. For solving these problems, many studies have been carried out until now, ranged from changing gradation to adding polymers and fibers to asphalt mixture. In this study, polypropylene additive was selected as fiber additive because of low costing and having good correlation with asphalt pavement. Three type of polypropylene additive in the length 6, 12 and 19 mm were selected and used at five different percentages in the asphalt concrete mixture. Asphalt specimens were analysed by Marshall Analysis and finally tested by Marshall Stability apparatus. Adding polypropylene increased Marshall Stability (38%), and decreased Flow (39%). These results show that polypropylene can be helpful for increasing pavement life.